Integrating Quranic insights with cognitive-behavioral support for adolescent depression: a spiritual-psychological framework - Mohiuddin, Mohammad (IIUM Press, 2025)
This study examines the approaches and frameworks found in the Qur’ān for addressing the growing issue of adolescent depression. A qualitative research method was adopted utilizing textual analysis to explore the Qur’ān, various tafsirs and scholarly interpretations, and existing research papers to identify relevant verses related to the depression issue. The study employed thematic coding, comparative and contextual analysis, and integration of perspectives. The research emphasizes three key strategies and supportive frameworks presented in the Qur’ān for managing adolescent depression: promoting positive behavioral change, spiritual enhancement and fostering supportive relationships. This study serves as a source of motivation for individuals and society to stay resilient, drawing strength from the Qur’anic wisdom. The paper also situates this integration within a broader Islamic civilizational perspective, arguing that the Qur’anic worldview offers therapeutic support and a holistic epistemology rooted in divine purpose and metaphysical coherence.